Participatory Multi-Criteria Decision-Making Analysis for Assessing the Potential of Ecotourism Development in Prespa Park - GRAZHDANI, Dorina (Journal of Environmental Management and Tourism; Vol 16 No 1 (2025): JEMT Volume XVI, Issue 1(77), Spring 2025, 2025)
In this study, an approach based on an integrated and participatory multi-criteria decision-making analysis was developed and used to identify the best option for tourism development and the main priority factors supporting the ecotourism industry in Prespa Park. The study was based on different empirical analyses and conducted in two parts. In the first part, the PROMETHE II technique coupled with a fuzzy Delphi survey was applied to identify the best type of tourism development. The obtained result indicated that the ecotourism option, was the best one, followed by agritourism, cultural tourism , rural tourism, and finally the "tourism as usual". In the second part, the ecotourism aspects were compared, and the main priority factors supporting the development of a sustainable ecotourism industry were identified using the fuzzy Delphi method and fuzzy analytical hierarchy process. Comparing various aspects of ecotourism, economics seems to be the main driver behind the industry, with social and environmental aspects coming in second and third. We also identified six priority factors supporting ecotourism, to which attention needs to be paid. The findings may aid policymakers and decision-makers in developing long-term strategies to boost the ecotourism industry and reduce environmental damage in Prespa Park and other similar areas.